PENGARUH PENDIDIKAN KESEHATAN HIPERTENSI TERHADAP TINGKAT KECEMASAN PADA PENDERITA HIPERTENSI DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Dewi Tiansa Barus (Jurnal Inovasi Kesehatan Masyarakat, 2022)
The success of changing anxiety in patients with hypertension depends not only on early detection, but also on understanding the underlying mechanism. One of the conditions that can cause anxiety in people with hypertension is lack of knowledge and stress. The purpose of this study was to determine the effect of hypertension on the level of anxiety in patients with hypertension at Grandmed Lubuk Pakam Hospital . This type of research uses the Quasy Experiment Method using the One-Group Pretest-Posttest Design research design. Determination of the sample is done by means of purposive sampling with sample seban yak 41 people. analysis was performed using the Paired Sample T Test with 95% confidence interval and the value of = 0.05. The results obtained from this study indicate a change in anxiety before and after being given hypertension health with a p-value = 0.000 (α < 0.05). In conclusion, there are Health Effects of Hypertension On The Level Anxiety In Patients with Hypertension Hospital GrandMed Lubuk pakam were conducted in accordance with the standards, For Health Institutions need for supervision and counseling to public that the importance of knowing the early signs of hypertension and its causes and treatment so as not to aggravate the condition patient.